Produção e degradação de plantas de cobertura de inverno em ambiente subtropical - Stefanello, Leonardo Sari (2024)
Soil cultivation with winter cover crops adds physical, chemical, and biological benefits to the grain production system. The effect of rapid and efficient soil coverage provides protection from rainfall, reducing the impact of water directly on the soil. The production of dry matter phytomass, together with its degradation time in the system, contribute to the cycling of nutrients and the development of microorganisms beneficial to the soil. The objective of this study was to evaluate the production of dry matter phytomass, the soil coverage curve of cover crops, and the decomposition curve of dry matter phytomass of cover crops in single crops and in a mix of cover crops in a subtropical environment. Experiments with black oats, rye, vetch, and forage turnip in single crops and in consortium (mix of cover crops) were conducted in Santa Maria - RS in 2022 and 2023 during the fall/winter period. The treatments T1 black oats, T2 rye, T3 vetch, T4 forage radish, T5 black oats + vetch, T6 black oats + forage radish, T7 black oats + vetch + forage radish, T8 rye + vetch, T9 rye + forage radish, T10 rye + vetch + forage radish. The evaluations performed were the speed of soil coverage, dry matter phytomass production in full flowering and evaluation of the degradation of these plant residues. Therefore, the dry matter phytomass production stood out for crops in cover crop mix, and the forage radish crop showed greater soil coverage and for a longer period of soil protection the use of black oats and rye.